Evaluación de los riesgos químicos por isómeros de dimetil benceno y su incidencia en la salud de los trabajadores de pintura de alto tráfico del Gad Municipalidad de Ambato. - Machado Miranda, Edgar Tarquino (2015)
This research is focused on the analysis and chemical risks assessment caused by volatile organic compounds (Xileno-M, Xileno-O, Xileno-P) in high traffic painting activities on Ambato Municipality. The importance of this research is given of these jobs are carried out every day being one of the most dangerous, and it may have unfavorable results on health workers by exposure to isomers of dimethyl benzene (Xylene), and also by the lack of chemical risks assessment and lack of knowledge of workers who perform these activities. The main objective is to assess chemical risks by isomers of dimethyl benzene and its impact on health workers of high traffic painting to decrease the workers exposure, as well as to motivate the responsibility of Municipality to develop the Security Health and Environment System and especially in chemical exposure area. This research will consider the use of the theory of chemical risks assessment based on the maximum acceptable exposure limits in the workplace according to the ACGIH TLV (American Conference of Governmental Industrial Hygienists) and using the concept NIOSH (National Institute for Occupational Safety and Health) to determine the exposure dose. The dose of volatile organic compounds in high traffic painting activities is additive, in this case is 1.75, is over the acceptable limit for humans that is 1, which causes serious diseases and the rate of morbidity is high. This study consist of a dangerous substances program prevention, where the techniques are based on acting on the source, the disease transmission and the worker.